-8(x+3)+2x+5=7x+9

Simple and best practice solution for -8(x+3)+2x+5=7x+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8(x+3)+2x+5=7x+9 equation:


Simplifying
-8(x + 3) + 2x + 5 = 7x + 9

Reorder the terms:
-8(3 + x) + 2x + 5 = 7x + 9
(3 * -8 + x * -8) + 2x + 5 = 7x + 9
(-24 + -8x) + 2x + 5 = 7x + 9

Reorder the terms:
-24 + 5 + -8x + 2x = 7x + 9

Combine like terms: -24 + 5 = -19
-19 + -8x + 2x = 7x + 9

Combine like terms: -8x + 2x = -6x
-19 + -6x = 7x + 9

Reorder the terms:
-19 + -6x = 9 + 7x

Solving
-19 + -6x = 9 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
-19 + -6x + -7x = 9 + 7x + -7x

Combine like terms: -6x + -7x = -13x
-19 + -13x = 9 + 7x + -7x

Combine like terms: 7x + -7x = 0
-19 + -13x = 9 + 0
-19 + -13x = 9

Add '19' to each side of the equation.
-19 + 19 + -13x = 9 + 19

Combine like terms: -19 + 19 = 0
0 + -13x = 9 + 19
-13x = 9 + 19

Combine like terms: 9 + 19 = 28
-13x = 28

Divide each side by '-13'.
x = -2.153846154

Simplifying
x = -2.153846154

See similar equations:

| 3+x+27=180 | | (2x+3)(4x-4)= | | [9(p+4)-18]-[2(p-4)+1]= | | 9(2k+3)+2=11(k-.5) | | .4x+7=.6x | | 2c-7=18 | | .8x-.2y-.1x-1.2y=.7 | | y-3/3-y-2/2=-1 | | 18/65=x/35 | | 9(q+9)= | | 13(4x+4)=3(5x+6) | | 5x=23+y | | 100(29)=10(29) | | 2xsquared-x=3 | | Y/9-6=-14 | | 5x+9=9+2x | | 8x-11/7=-5 | | z/15-6=14 | | 3x-12=-4x+32 | | v=(p*q)-((p*q)/100*5)-p | | -2=6/8 | | 3(16-4y)4y=8 | | 8-9s+s^2= | | 1015=2x+5 | | 4-3d=8 | | -9x-6=-3(3x+2) | | d=2m+3m | | 4x+5x(-5)=21 | | 3(2n-5)=-7-2 | | -2p-5(6-2p)=5(p-2)-26 | | 3/4(a-5)=9 | | 367=4x+5 |

Equations solver categories